Unit non-response in household wealth surveys: Experience from the Eurosystem's Household Finance and Consumption Survey - Guillaume Osier (European Central Bank (ECB), 2016)
The Household Finance and Consumption Survey (HFCS) is a recent initiative from the Eurosystem to collect comparable micro-data on household wealth and indebtedness in the euro area countries. The Household Finance and Consumption Network (HFCN), which comprises the European Central Bank (ECB), national central banks (NCBs), and national statistical institutes (NSIs), is in charge of the development and implementation of the HFCS. The first round of the survey was successfully conducted between 2008 and 2011, and the results were published in April 2013. The second round is now under way and will cover all the euro area countries. This paper is a joint effort by several members of the HFCN to further investigate the issue of unit non-response in the HFCS, better describe and understand its patterns, measure its effects on the overall quality of the survey and, ultimately, propose strategies to mitigate them. The paper is divided into sections, the first section being the introduction. The second section draws up a list of the main possible sources of auxiliary information that can be relied on in order to analyse non-response patterns in the HFCS. It also presents summary indicators that can be used to quantify unit non-response. In the third section, based on the experience from the first wave of the HFCS, the report elaborates on good survey practices (e.g. interviewer training and compensation, use of incentives, persuasive contact strategies, etc.) to prevent unit non-response from occurring. The fourth section compares several reweighting strategies for coping with unit non-response a posteriori, in particular simple and generalised calibration methods. These methods are assessed with respect to their impact on the main HFCS-based estimates. Finally, based on the outcome of this empirical analysis, recommendations are made with regard to post-survey weighting adjustment in the HFCS.
Keywords: C83; 330; calibration; response propensity; sampling weights; unit non-response